Comparison of Some Extraction Methods for Isolation of Catechins and Caffeine from Turkish Green Tea - Ezgi DEMİR (International Journal of Secondary Metabolite, 2015)
Effective extraction of anticancer and antioxidant principles from Turkish green tea were main purpose of this work. The pre-optimized experimental condition for liquid extraction was employed for comparative appraisal. Not only extraction methods also nature of the green tea samples (fresh, dried or frozen) and quantitative yields related to collection periods were investigated. After extraction of the green tea with various techniques the extract was partitioned with chloroform to remove caffeine, after that the extract was partitioned with ethyl acetate to obtain catechin mixture. Quantification of individual catechins was carried out by HPLC and analysis results proved that epigallocatechin gallate (EGCG) was main catechin specie present in all extracts. The results indicate that hot water extraction (at 80 0C) provides higher catechin yield when compared to other methods. The highest extract yields were obtained with dried leaves collected in second collection period. The crude catechin mixture contains high amount of EGCG and might be used as raw material for production of plant remedies at industrial scale.